Concept Analysis: Compliance Among Diabetic Patients - Parliani Parliani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
There is a lot of evidence showing that the level of compliance is a fundamental factor in determining the health status of people with diabetes mellitus. Although many treatments have been effective in treating this disease, there are still many patients who fail to achieve glycemic control which causes complications and premature death. The purpose of this analysis concept is to clarify the concept of compliance with diabetes mellitus patients so that it becomes the basis for understanding in decision making in avoiding complications and long-term adherence in diabetes management. This concept analysis uses eight methods of 8 step walker and avant from 11 articles reviewed. Compliance in carrying out antidiabetic therapy is an active participation of patients on an ongoing basis in carrying out the use of drugs, diet and exercise. The concept of this analysis serves to direct the mindset of nurses in determining standard guidelines and improving adherence to the regimen of diabetic patients.